PENGEMBANGAN DESAIN ALAT REBUS ECOPRINT 2 (APEc_2) UNTUK MENINGKATKAN PRODUKTIFITAS PADA IKM “CITRA COLLECTION” KOTA TEGAL: DESIGN DEVELOPMENT BOILTING TOOL OF ECOPRINT 2 (APEc_2) TO INCREASING PRODUCTIVITY AT IKM "CITRA COLLECTION" TEGAL - Tofik Hidayat; Zuffah Zuffah; Siswiyanti Siswiyanti (Teknika, 2023)
This research is a development of previous research with the ecoprint boiling tool (APEc_1), this tool has been used by the company for the ecoprint production process. The development of demand for products such as shoes, bags and wallets made from ecoprint leather has increased quite well. It turns out that this condition is sometimes not followed by the availability of leather raw materials that have been diecoprinted. APEc_1 is only able to produce 2 pieces at a time by boiling with a duration of 2 hours, so if this tool is used continuously, in one working day it is only able to produce 8 sheets of eciprint skin. Another complaint is that this tool cannot be used for the process of boiling fabric raw materials. Boiling cloth requires a higher temperature with a duration of 2.5 hours. This study uses an experimental method with a creative rational approach. This method is quite simple but gives optimal results for simple cases and not many product forming variables. The dimensions of the ecoprin 2 boiling device (APEc_2) are designed using the dimensions of a two-burner stove for length and width measurements. As for the height of the tool using general anthropometric dimensions, the tool dimensions are still the same as APEc_1. With the creative rational method the researcher paid attention to the dimensions of the "lontong" circle in APEc_1, and obtained data that there was still a large enough space to be utilized by increasing the number of rolls from 2 to 5. The addition of a roll changes the shape of the lid which was initially tilted to a straight one so that you can add a "lontong" roll. The result of this research is the APEc_2 boiling device with a total of 5 rolls, and can be rotated simultaneously using a crank on one of the rolls connected to the connecting chain of the other rolls. The roll is made of steenless pipes, so APEc_2 can be used for the boiling process of raw leather and fabric raw materials, and boiling can be done together, with this function, APEc_2 is a multi-functional ecoprint boiling tool. Keywords: Ecoprint, IKM, Creative Rationale, Lontong, APEc_2